High-concentration tramadol-induced vasodilation in rabbit aorta is mediated by both endothelium-dependent and -independent mechanisms. - Kaya Tijen; Gursoy Sinan; Karadas Baris; Sarac Bulent; Kafali Haluk; Soydan Ahmet Serdar (Acta Pharmacologica Sinica, 2016)
AIM: The mechanism of tramadol-induced vasodilation was investigated using isolated rabbit thoracic aortic rings. METHODS: Aortic rings from 8 rabbits were placed in organ bath and precontracted with phenylephrine (10(-5) mol/L) before addition of tramadol. Relaxation responses by tramadol were evaluated in the presence and absence of endothelium, indomethacin (an inhibitor of cyclooxygenase), NG-nitro-L-arginine methyl ester (L-NAME, a specific inhibitor of nitric oxide synthase), glibenclamide (an inhibitor of ATP-sensitive potassium channels), tetraethylammonium chloride (TEA, an inhibitor of calcium-sensitive potassium channels), and naloxone (an antagonist of opioid receptors). RESULTS: Tramadol (10(-4) mol/L and 3 x 10(-4) mol/L) caused significant vasodilation in endothelium-intact and endothelium-denuded aortic rings (P